Whole‐body imaging of adoptively transferred T cells using magnetic resonance imaging, single photon emission computed tomography and positron emission tomography techniques, with a focus on regulatory T cells. (10th April 2013) - Leech, J. M.; Sharif‐Paghaleh, E.; Maher, J.; Livieratos, L.; Lechler, R. I.; Mullen, G. E.; Lombardi, G.; Smyth, L. A.
Summary Cell‐based therapies using natural or genetically modified regulatory T cells (Tregs) have shown significant promise as immune‐based therapies. One of the main difficulties facing the further advancement of these therapies is that the fate and localization of adoptively transferred Tregs is largely unknown. The ability to dissect the migratory pathway of these cells in a non‐invasive manner is of vital importance for the further development of in‐vivo cell‐based immunotherapies, as this technology allows the fate of the therapeutically administered cell to be imaged in real time. In this review we will provide an overview of the current clinical imaging techniques used to track T cells and Tregsin vivo, including magnetic resonance imaging (MRI) and positron emission tomography (PET)/single photon emission computed tomography (SPECT). In addition, we will discuss how the finding of these studies can be used, in the context of transplantation, to define the most appropriate Treg subset required for cellular therapy.